Quantifying the Volume of Particulate Matter at Bus Stations - Branislav ŠARKAN; Michal LOMAN; Ondrej STOPKA; Jacek CABAN; Arkadiusz MAŁEK (Promet (Zagreb))
Congested urban traffic substantially contributes to air pollution in cities. While waiting at bus stops, passengers may be exposed to increased contamination caused by vehicles, including particulate matter (PM). The modern bus stop layout, position and design ignore air quality and allow excessive exposure to pollution. Particulate matter seriously harms the environment, threatening human health and severely damaging all living organisms. The research purpose is to monitor particle emissions at the bus station in the city of Žilina (Slovakia), amassing data on exhaust emissions released from buses at the station premises. As moving or running-engine vehicles incessantly produce atmospheric emissions, we measure air quality during peak hours at the bus station. The results indicate a direct interconnection between passing vehicles and produced particle emissions, when multiple times higher emission levels are revealed. During the morning rush hour, the particulate matter exceeded 360% for PM2.5 and 420% for PM10. The research showed PM released directly from the buses tends to accumulate in covered premises of the bus station, severely damaging the health of passengers and staff. Our study warns about possible risks of deteriorating human health as waiting passengers unknowingly inhale contaminated particles. Our results indicate the largest emission producers and suggest remedial measures.